Simian virus 40 integration sites in the genome of virus-transformed mouse cells. - Prasad, I (1975)
To gain information on the specificity of simian virus 40 (SV40) integration in the genome of transformed cells, mouse 3T3 cells were transformed by a temperature-sensitive (ts) SV40 mutant, using high multiplicity of infection (MOI). Transformed cells were superinfected with wild-type (wt) virus at high MOI. Clones were isolated and fused with permissive BSC-1 cells to promote virus rescue. All rescued viruses were of the ts type only. When the high-MOI transformants were infected with 3H-labeled wt SV40, the amount of radioactivity associated with their nuclear fraction was found to be similar to that of 3T3 cells. 3T3 cells were then transformed by ts SV40 at low MOI and superinfected by wt virus at high MOI. Upon fusion with BSC-1 cells, most clones produced both ts and wt virus. These results suggest that the number of stable SV40 integration sites in the 3T3 genome is limited, since they can be saturated by transformation at high MOI. When the MOI is low, the sites are not saturated and a subsequent infection can lead to integration.